Linguistic diversity and ecology of the Northern and South – Western Region of Sarawak, East Malaysia, Borneo - Norahim, Norazuna (Universiti Malaysia Sarawak, 2013)
This paper is an attempt to provide an overview of the state of the linguistic diversity and ecology of the state of Sarawak, East Malaysia. The existence of multilingualism/ bilingualism is not evenly distributed throughout the region. This will be examined from various dimensions such as rural-urban, geographical and demographic. The paper also highlights past and current research projects on threatened and endangered languages of Sarawak, and includes a discussion on retention (if not revival) of minority languages. A particular focus of this paper is to examine the causes for changes in language choice patterns observed in some communities. In multilingual communities in the region, attitudes towards languages and the types of bilingual practices - how speakers utilise languages within their repertoires, have been proven to be the main causes of a community or a social group within the community to initiate changes in language choice patterns that may threaten the survival of minority community languages.